Effects of Vitamin D3 Supplementation on Cardiovascular and Cancer Outcomes by eGFR in VITAL. Issue 12 (29th December 2022) - Limonte, Christine P.; Zelnick, Leila R.; Hoofnagle, Andrew N.; Thadhani, Ravi; Melamed, Michal L.; Mora, Samia; Cook, Nancy R.; Luttmann-Gibson, Heike; Sesso, Howard D.; Lee, I-Min; Buring, Julie E.; Manson, JoAnn E.; et al.
Visual Abstract: Abstract : Key Points: Baseline eGFR does not affect the effects of supplementation with vitamin D3 on the incidence of cardiovascular events or invasive cancer. Vitamin D3 supplementation results in a greater reduction in serum parathyroid hormone concentration in those with lower versus higher eGFR. Background: Reduced 25-hydroxyvitamin D (25[OH]D) metabolism and secondary hyperparathyroidism are common with lower estimated glomerular filtration rate (eGFR) and may contribute to cardiovascular disease and cancer risk. Methods: We assessed for heterogeneity by baseline eGFR of the effects of vitamin D3 on cardiovascular and cancer outcomes in the Vitamin D and Omega-3 Trial (VITAL). Participants were randomized to 2000 IU vitamin D3 and/or 1 g Ω -3 fatty acids daily using a placebo-controlled, two-by-two factorial design (5.3 years follow-up). Primary study end points were incident major cardiovascular events and invasive cancer. Changes in serum 25(OH)D and parathyroid hormone (PTH) were examined. Results: Baseline eGFR was available for 15, 917 participants. Participants' mean age was 68 years, and 51% were women. Vitamin D3 resulted in higher serum 25(OH)D compared with placebo (difference in change 12.5 ng/ml; 95% CI, 12 to 13.1 ng/ml), without heterogeneity by eGFR ( P interaction, continuous eGFR=0.2). Difference in change in PTH between vitamin D3 and placebo was larger with lower eGFR ( P interaction=0.05): –6.9 (95% CI, –10.5 to –3.4), –5.8 (95% CI, –8.3 to –3.4), –4 (95% CI, –5.9 to –2.2), and –3.8 (95% CI, –5.6 to –2) pg/ml for eGFR <60, 60–74, 75–89, and ≥90 ml/min per 1.73 m 2, respectively. Effects of vitamin D3 supplementation on cardiovascular events ( P interaction=0.61) and cancer ( P interaction=0.89) did not differ by eGFR: HR=1.14 (95% CI, 0.73 to 1.79), HR=1.06 (95% CI, 0.75 to 1.5), HR=0.92 (95% CI, 0.67 to 1.25), and HR=0.92 (95% CI, 0.66 to 1.27) across eGFR categories for cardiovascular events and HR=1.63 (95% CI, 1.03 to 2.58), HR=0.85 (95% CI, 0.64 to 1.11), HR=0.84 (95% CI, 0.68 to 1.03), and 1.11 (95% CI, 0.92 to 1.35) for cancer, respectively. Conclusions: We observed no significant heterogeneity by baseline eGFR in the effects of vitamin D3 supplementation versus placebo on cardiovascular or cancer outcomes, despite effects on 25(OH)D and PTH concentrations.